2023
DOI: 10.1002/acn3.51833
|View full text |Cite
|
Sign up to set email alerts
|

Neurological diagnoses in hospitalized COVID‐19 patients during the B.1.1.529 surge

Abstract: ObjectiveEmerging variants and sublineages of SARS‐CoV‐2 have differing disease severity, transmissibility, and immune evasion. The neurological conditions associated with the original strain of SARS‐CoV‐2 are well established. Our study assessed the neurological presentations specific to hospitalized patients during the B.1.1.529 (Omicron) variant surge in New York City.MethodsA total of 178 cases with positive RT‐PCR result within 6 weeks before admission, and subsequent development of select neurological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Among younger individuals, a rise in neurologic symptoms, such as altered mental status and seizures, was also observed when the Omicron variant emerged ( 18 , 19 ). This is consistent with the findings of another study, which stratified subjects into pre-Omicron and post-Omicron surge groups and demonstrated that encephalopathy is the most common neurologic diagnosis among both variants ( 11 ). The frequency of stroke and seizure was higher among post-Omicron surge patients compared to pre-Omicron patients ( 11 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among younger individuals, a rise in neurologic symptoms, such as altered mental status and seizures, was also observed when the Omicron variant emerged ( 18 , 19 ). This is consistent with the findings of another study, which stratified subjects into pre-Omicron and post-Omicron surge groups and demonstrated that encephalopathy is the most common neurologic diagnosis among both variants ( 11 ). The frequency of stroke and seizure was higher among post-Omicron surge patients compared to pre-Omicron patients ( 11 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the findings of another study, which stratified subjects into pre-Omicron and post-Omicron surge groups and demonstrated that encephalopathy is the most common neurologic diagnosis among both variants ( 11 ). The frequency of stroke and seizure was higher among post-Omicron surge patients compared to pre-Omicron patients ( 11 ). Our study was conducted during the pre-Omicron and Omicron waves and demonstrated that approximately 30% of patients with a stroke died in the hospital.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Between 2021 and 2023, a total of 61 manuscripts were authored by our alumni, including 27 original research articles, 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 16 case reports, 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 2 perspective pieces, 50 51 3 review articles, 52 53 54 1 book chapter, 55 1 association statement, 56 1 consensus statement, 57 1 data note, 58 and 8 that were published on a preprint server (not peer reviewed). 59 60 61 62 63 64 65 Of these academic contributions, 19 of these papers were published in journals with an impact factor of 3.0 to 10.0.…”
Section: Impact Of the Neurology Training Programmentioning
confidence: 99%